2014
DOI: 10.1111/eth.12219
|View full text |Cite
|
Sign up to set email alerts
|

Prey Responses to Predator's Sounds: A Review and Empirical Study

Abstract: Many animals assess their risk of predation by listening to and evaluating predators' vocalizations. We reviewed the literature to draw generalizations about predator discrimination abilities, the retention of these abilities over evolutionary time, and the potential underlying proximate mechanisms responsible for discrimination. Broadly, we found that some prey possess an ability to respond to a predator after having been evolutionarily isolated from a specific predator (i.e., predators are allopatric) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
80
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(94 citation statements)
references
References 75 publications
6
80
0
Order By: Relevance
“…Thus, we expected to see the highest stress levels and the lowest activity in treatments with variable temperature and predatory cues. In stable temperature treatments with non-predatory bird sounds the activity was expected to stay species-typical and stress levels low , Hettena et al 2014. …”
mentioning
confidence: 99%
“…Thus, we expected to see the highest stress levels and the lowest activity in treatments with variable temperature and predatory cues. In stable temperature treatments with non-predatory bird sounds the activity was expected to stay species-typical and stress levels low , Hettena et al 2014. …”
mentioning
confidence: 99%
“…Playback experiments can and have been used to test the behavioural responses of animals to an enormous range of sounds, including the vocalizations of other animals (Hettena, Munoz & Blumstein ; King ), and anthropogenic noises (Francis & Barber ); and camera traps provide the means to remotely observe virtually any animal in the wild (Hamel et al . ; Burton et al .…”
Section: Discussionmentioning
confidence: 99%
“…), dogs (e.g., raccoons, Suraci et al . ), anthropogenic noise (Francis & Barber ), predators (180 experiments on everything from toads to elephants, reviewed in Hettena, Munoz & Blumstein ), competitors (e.g., black bears and cougars, Suraci et al . ; hyenas and African wild dogs, Webster, McNutt & McComb ), potential mates (e.g., lions, McComb et al .…”
Section: Introductionmentioning
confidence: 99%
“…Animals should use any available information to assess the risk of predation, and many species have evolved the ability to respond to sounds that are associated with risk. Such information may come directly from the sounds that predators produce (e.g., Hettena, Munoz, & Blumstein, 2014), indirectly from alarm calls produced by conspecifics (e.g., Klump & Shalter, 1984), or indirectly from alarm calls produced by similarly vulnerable members of other species (Magrath, Haff, Fallow, & Radford, 2015). Taken together this literature has shown that many species capitalize on available acoustic information to improve their assessments of risk, and that even species that do not produce sounds are able to respond to acoustic cues of risk (Huang, Lubarsky, Teng, & Blumstein, 2011;Vitousek, Adelman, Gregory, & St. Clair, 2007).…”
Section: Introductionmentioning
confidence: 99%